Global Anti-Terrorism Law and Policy - Ramraj, Victor V.; Hor, Michael; Roach, Kent; Williams, George (Cambridge University Press, 2012)
Preventing acts of terrorism remains one of the major tasks of domestic governments and regional and international organisations. Terrorism transcends borders, so anti-terrorism law must cross the boundaries of domestic, regional and international law. It also crosses traditional disciplinary boundaries between administrative, constitutional, criminal, financial, immigration, international and military law, as well as the law of war. This second edition provides a comprehensive resource on how domestic, regional and international responses to terrorism have developed since 2001. Chapters that focus on a particular country or region in the Americas, Europe, Africa and Asia are complemented by overarching thematic chapters that take a comparative approach to particular aspects of anti-terrorism law and policy .